2012
DOI: 10.2320/matertrans.m2011368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain Boundary Resistivity on Solid State Phase Transformation Induced by Electric Current Pulse in a Cold-Rolled Cu–Zn Alloy

Abstract: To clear the effect of grain boundary resistivity on solid state phase transformation, an electrical current pulse (ECP) was applied to a 40% cold-rolled CuZn alloy, and the angle between the exerted current direction (CD) and rolling direction (RD) varied from 0 to 90°. Results showed that with the change of angle, the average grain sizes of ECP treated samples were varied. Through the thermodynamic analysis, it was known that the different diffusion activation energy induced by different grain boundary resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…11,12 Wang observed that the average grain sizes of Cu-Zn alloys varied with the change of angle between current direction and rolling direction, because the resistivity of different grain boundaries gave rise to different diffusion activation energy. 13 Jiang revealed that electropulsing dramatically enhanced the dissolution rate of b-Mg 17 Al 12 precipitates in AZ91 magnesium alloy. 14 Huang found that electropulsing significantly reduced the a fi b phase transformation temperature in Ti-6Al-4 V alloy and accelerated phase transformation rate because the energy barriers of both nucleation and growth of the new b phase were reduced.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Wang observed that the average grain sizes of Cu-Zn alloys varied with the change of angle between current direction and rolling direction, because the resistivity of different grain boundaries gave rise to different diffusion activation energy. 13 Jiang revealed that electropulsing dramatically enhanced the dissolution rate of b-Mg 17 Al 12 precipitates in AZ91 magnesium alloy. 14 Huang found that electropulsing significantly reduced the a fi b phase transformation temperature in Ti-6Al-4 V alloy and accelerated phase transformation rate because the energy barriers of both nucleation and growth of the new b phase were reduced.…”
Section: Introductionmentioning
confidence: 99%